2017
DOI: 10.1021/acs.iecr.7b02877
|View full text |Cite
|
Sign up to set email alerts
|

Role of Citric Acid in Preparing Highly Active CoMo/Al2O3 Catalyst: From Aqueous Impregnation Solution to Active Site Formation

Abstract: In this work, the role of citric acid (CA) in preparing CoMo/Al 2 O 3 catalyst was investigated from aqueous impregnation solution to catalytic active site formation by laser Raman, UV−vis, in situ IR and mass spectrometry characterizations. COS and CO were employed as probe molecules to illustrate the formation of active site during and after catalyst sulfidation, respectively. Citric acid mainly coordinates with Mo, resulting in the presence of Mo−CA complex, which consequently enlarge the temperature window… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…The CoMoS edge sites of these catalysts were in-situ characterized by lowtemperature CO adsorption followed by IR spectroscopy [12,19,21,22]. First, the dried catalytic precursor in oxidic form was grounded and pressed into a self-supported wafer (10 mg for a disc of 2.01 cm 2 ) precisely weighted and positioned into a quartz IR cell with CaF2 windows.…”
Section: Low-temperature Co Adsorption Followed By Ir Characterization (Ir/co)mentioning
confidence: 99%
See 3 more Smart Citations
“…The CoMoS edge sites of these catalysts were in-situ characterized by lowtemperature CO adsorption followed by IR spectroscopy [12,19,21,22]. First, the dried catalytic precursor in oxidic form was grounded and pressed into a self-supported wafer (10 mg for a disc of 2.01 cm 2 ) precisely weighted and positioned into a quartz IR cell with CaF2 windows.…”
Section: Low-temperature Co Adsorption Followed By Ir Characterization (Ir/co)mentioning
confidence: 99%
“…Low-temperature (liquid nitrogen temperature) CO adsorption followed by in situ IR spectroscopy (IR/CO) allows distinguishing non-promoted (MoS2) sites and promoted (CoMoS) sites [19,23,24] on the supported CoMo catalyst. Figure 1 reports the IR/CO spectra obtained on the CoMo(CA/M = x)/Al2O3 catalysts.…”
Section: Ir/co Characterizations Of Sulfided Como(ca/m =0 and 2)/al2o3 Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, Scheffer et al [26] suggested that the higher activity of CoMoS phase is attributed to the weaker active phase-support interaction. In the same way Chen et al showed that addition of chelating agent as citric acid limits the metal support interaction and leads to the formation of more active M and CoMo catalysts [17,27]. Consequently, the catalyst NiW with chelating agent could forms NiWS species more active than NiW.…”
Section: Temperature Programmed Reductionmentioning
confidence: 94%